2008
DOI: 10.1590/s0102-33062008000100024
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização florística de comunidades vegetais de restinga em Bertioga, SP, Brasil

Abstract: O município de Bertioga, no litoral central do Estado de São Paulo, apresenta grandes extensões de restingas ainda preservadas, com reduzido número de coletas de material botânico. A rápida devastação desse tipo de ambiente, por pressão de empreendedores do ramo imobiliário e outras intervenções antrópicas, torna urgente a compilação de dados que subsidiem estratégias conservacionistas. Nesse aspecto, é aqui apresentada a caracterização florística das comunidades vegetais da região que abrange as restingas de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
32

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 7 publications
4
30
1
32
Order By: Relevance
“…The species richness of the study areas were found to be similar to those of other Restinga forest surveys (Martins et al 2008;Castro et al 2012), but approximately three times lower than neighboring wet forest formations of the Atlantic domain (Amorim et al 2008;Amorim et al 2009 et al (2005) environmental filters that limit the establishment of lineages not adapted to the unique conditions of Restinga habitats. The most species rich families encountered in our surveys (Fabaceae, Myrtaceae, Sapotaceae, and Rubiaceae) were also among the most important families reported in other Restinga forest sites (Assumpção & Nascimento 2000;Assis et al 2004;Martins et al 2008;Silva et al 2008).…”
Section: The Floras Of the Southern Bahia Restinga Forestssupporting
confidence: 69%
See 3 more Smart Citations
“…The species richness of the study areas were found to be similar to those of other Restinga forest surveys (Martins et al 2008;Castro et al 2012), but approximately three times lower than neighboring wet forest formations of the Atlantic domain (Amorim et al 2008;Amorim et al 2009 et al (2005) environmental filters that limit the establishment of lineages not adapted to the unique conditions of Restinga habitats. The most species rich families encountered in our surveys (Fabaceae, Myrtaceae, Sapotaceae, and Rubiaceae) were also among the most important families reported in other Restinga forest sites (Assumpção & Nascimento 2000;Assis et al 2004;Martins et al 2008;Silva et al 2008).…”
Section: The Floras Of the Southern Bahia Restinga Forestssupporting
confidence: 69%
“…The most species rich families encountered in our surveys (Fabaceae, Myrtaceae, Sapotaceae, and Rubiaceae) were also among the most important families reported in other Restinga forest sites (Assumpção & Nascimento 2000;Assis et al 2004;Martins et al 2008;Silva et al 2008). Myrtaceae taxa are typically found on soils with low fertility (Berry 1915) and are important components of Restinga vegetation along the entire coast of Brazil.…”
Section: The Floras Of the Southern Bahia Restinga Forestsmentioning
confidence: 51%
See 2 more Smart Citations
“…Já as famílias com maior número de indivíduos foram Myrtaceae (com 116 indivíduos, 32,1% do total amostrado), Erythroxylaceae (92, 25,5%) e Celastraceae (35, 9,8%) que, juntas, corresponderam a 68,2% dos indivíduos amostrados, enquanto as outras 9 somaram 31,7% (111 indivíduos). Estes dados corroboram os estudos realizados por Sugiyama (2003), Assis et al (2004) (Martins et al 2008). Tabela 3.…”
Section: Resultsunclassified